2020
DOI: 10.3390/molecules25061294
|View full text |Cite
|
Sign up to set email alerts
|

Thermally-Induced Lactosylation of Whey Proteins: Identification and Synthesis of Lactosylated β-lactoglobulin Epitope

Abstract: The high temperatures used in the production of milk may induce modifications in proteins structure. Due to occurrence of the Maillard reaction, lactose binds lysine residues in proteins, affecting the nutritional value. Milk is also an important source of allergenic proteins (i.e., caseins, β-lactoglobulin and α-lactalbumin). Thus, this modification may also affect the allergenicity of these proteins. Focusing on milk whey proteins, a screening on different Ultra High Temperatures (UHT) and pasteurized milk s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…In previous studies [15][16][17][18][19][20][21][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], the focus was on developing a specific handler for a specific domain for ATE parallel testing. However, in a situation of existing different domains such as electrostatic, piezoelectric, and piezoresistive, a methodology capable of handling all the domains are required.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies [15][16][17][18][19][20][21][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], the focus was on developing a specific handler for a specific domain for ATE parallel testing. However, in a situation of existing different domains such as electrostatic, piezoelectric, and piezoresistive, a methodology capable of handling all the domains are required.…”
Section: Methodsmentioning
confidence: 99%
“…Computed Tomography (CT) is another solution for taking internal photos, but simplicity and high throughput is the main drawback in front of this technology [36]. Transmission Electron Microscopy (TEM), Energy-Dispersive X-ray Spectroscopy (EDS) [38], Wavelength-Dispersive X-ray Spectroscopy (WDS) [39], Infrared Microscopy [40], and Thermally Induced Voltage Alteration (TIVA) [41] are some of the methods for MEMS material testing and chemical composition evaluation that are non-destructive. These methods are also not too cheap to be used in highly parallel sensor and actuator testing, while the AbFM is a cheap solution that can be adopted to test MEMS devices at wafer-level scale.…”
Section: Destructive Non-destructivementioning
confidence: 99%
See 1 more Smart Citation
“…However, these observations are based on studies of undigested milk proteins and not of linear epitopes exclusively, and thus can probably not be extrapolated for all MRPs and peptides. A study by Gasparini et al [46] reported an approach creating the basis for studying the effect of lactosylation on linear epitopes. However, data comparing sIgE binding of lactosylated vs. non-modified peptides is not available at this time.…”
Section: Effect Of Heat Treatment On Identification Of Ige Binding Epmentioning
confidence: 99%
“…Therefore, an extrapolation of these findings to any peptide and any kind of modification is probably not possible. With respect to the potential immunological consequences, it is suggested that glycation if present on a linear sIgE binding epitope can affect the interaction between the peptide and the antibody [46]. Moreover, AGEs themselves have also been reported to modulate inflammatory pathways by binding to receptors for AGEs [14].…”
Section: Identification Of Peptides On the Basolateral Side Of The Camentioning
confidence: 99%